PENGARUH TANGGUNG JAWAB SOSIAL PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN RASIO PROFITABILITAS SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN TERBUKA YANG TERCATAT DALAM INDEKS SRI KEHATI DI BEI PADA PERIODE 2010 - 2020 - Y.B. Suhartoko; Leonardus Herjuno Perwiro (Universitas Katolik Indonesia Atma Jaya, 2023)
This study aimed to analyze the influence of CSR on CVs, analyze the influence of profitability on and analyze the influence of profitability as a moderation variable on the relationship between CSR and CV. This study used a data analysis panel of 9 issuer companies in the SRI-Kehati index from 2010 to 2020. In this study, partial CSR could not influence the CV. The results showed that when interacting with CSR, ROE will affect the relationship between CSR and CV significantly and positively. In other words, it can also be concluded that profitability (ROE) can moderate the relationship between CSR and CV. Thus, CSR does not directly affect the CV; other supporting factors such as ROE are needed to influence CSR to affect the CV.